1982
DOI: 10.1213/00000539-198208000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Perioperative Complications during Carotid Endarterectomy

Abstract: Factors associated with perioperative complications during carotid endarterectomy. Anesth Analg 1982;61:631-7.Records from 166 cases of unilateral carotid endarterectomy were reviewed to investigate the association of certain preoperative and intraoperative factors with perioperative complications including hypertension and hypotension, neurologic deficit, myocardial infarction, and mortality. No myocardial infarctions occurred and mortality was zero.Complications associated with some of the study factors incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2

Year Published

1984
1984
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(16 citation statements)
references
References 8 publications
0
14
2
Order By: Relevance
“…Patients with lesser degrees of untreated hypertension (diastolic pressures >90mmHg but <110mmHg), or those whose high arterial pressure was well controlled by antihypertensive drugs, showed no increase of postoperative morbidity compared with their nonnotensive counterparts (Goldman and Caldera, 1979). In specific areas of surgery, notably carotid endarterectomy (Asiddao et al, 1982), the pre-existence of inadequately controlled hypertension has been clearly shown to be associated with an increased frequency of both transient and permanent neurological deficit. Pre-existing hypertension has been shown to increase the occurrence of postoperative myocardial re-infarction in patients who had a history of previous myocardial infarction (Steen, Tinker and Tarhan, 1978).…”
Section: Anaesthesia Surgery and Hypertensionmentioning
confidence: 96%
“…Patients with lesser degrees of untreated hypertension (diastolic pressures >90mmHg but <110mmHg), or those whose high arterial pressure was well controlled by antihypertensive drugs, showed no increase of postoperative morbidity compared with their nonnotensive counterparts (Goldman and Caldera, 1979). In specific areas of surgery, notably carotid endarterectomy (Asiddao et al, 1982), the pre-existence of inadequately controlled hypertension has been clearly shown to be associated with an increased frequency of both transient and permanent neurological deficit. Pre-existing hypertension has been shown to increase the occurrence of postoperative myocardial re-infarction in patients who had a history of previous myocardial infarction (Steen, Tinker and Tarhan, 1978).…”
Section: Anaesthesia Surgery and Hypertensionmentioning
confidence: 96%
“…Although CEA has been a standard method of treatment for carotid artery stenosis, haemodynamic instability after CEA has been linked to surgical morbidity and mortality 4,5,6,7 . CEA -induced hypotension has been demonstrated to correlate with poor outcome, as extensively described in the literature 8,9,10 .…”
Section: Discussionmentioning
confidence: 99%
“…Although no data exist on the relationships between preoperative and intraoperative tachycardia, and preoperative tachycardia and complications, previous studies have found associations between preoperative and intraoperative BP, and preoperative BP and perioperative complications. [11][12][13] It is therefore possible that a similar relationship exists for preoperative and intraoperative HR. For preoperative tachycardia due to a known etiology (e.g., pain or anxiety), appropri-ately treating the causative factor should eliminate this association.…”
Section: Discussionmentioning
confidence: 99%